Resilience in sophisticated financial crime networks: a social network analysis of the Madoff Investment Scheme - Hardy, John (Crime prevention and community safety, 2020)
Despite numerous investigations and studies, the resilience of Madoff’s scheme from at least the 1970s until its collapse in 2008 is poorly understood. This study applies social network analysis (SNA) to the Madoff Investment Scheme in order to identify key factors which support resilience in networks that are engaged in a sophisticated criminal enterprise. The SNA identified four clusters of individuals who performed vital functions within the network: a core leadership group, a compliance group, a capital group and a facilitators group. The study then examined the network’s response to exogenous and endogenous shocks, finding that the Madoff network had been resilient to both exogenous shocks, such as Securities and Exchange Commission examinations, and endogenous shocks, such as significant investor withdrawals, prior to its collapse in 2008. These findings suggest that monitoring network responses to exogenous and endogenous shocks could assist investigators in identifying Ponzi schemes in the future.